Corrosion Effect of X70 Pipeline External Surface Under Sedentary and Peat Soil Environment - Mohamad NorDin, Nurul Izzah (Enhanced Knowledge in Sciences and Technology, 2022)
: Soil characteristics and environmental conditions of surrounding both impact the corrosion of subterranean pipes, particularly on their exposed surfaces. Due to friable spots and corrosion prevention failure, corrosion of the external oil and gas pipeline might result in a catastrophic catastrophe in the oil refinery sectors, limiting pipeline performance under high-pressure scenarios. In addition, this problem might cost the sector a lot of money, especially in terms of pipeline upkeep. The surface morphology modification of this external pipeline was investigated in this work under a number of exposure intervals (7 and 14 days) in sedentary soil and acidic peat soil. Organic peat soil with a pH range of between 4.5 to 5.5 was chosen since it has the potential to cause surface degradation on the pipeline’s exterior. It was also investigated the corrosion behavior of X70 steel pipeline buried in a sedentary soil environment. Scanning Electron Microscopy-Energy Dispersive X-ray Microscopy (SEM-EDX) was used to investigate the surface morphology and elemental distribution of the corrosion effect on external surface of X70 steel pipeline. On the surface of X70 steel, SEM pictures indicated the formation of dispersive corroded deposits and microscopic irregular porosity, while EDX confirmed the presence the elements of Fe, O, and C associated with corrosion products. This phenomenon was primarily caused by intergranular corrosion throughout this pipeline, which led in the gradual induction of non-uniform and pitting corrosion products.